Application of multi-dimensional team cooperation management in reducing the number of patient companions in the emergency ward during the COVID-19 outbreak (新型冠状病毒肺炎疫情防控期间运用多维度团队协作管理模式减少急诊病房陪护人数的实践) - CHEN Jiachun (陈佳春); SHI Hailiu (施海柳); PENG Lei (彭蕾) (中西医结合护理)
This paper summarized the strategies and practice of multi-dimensional team cooperation management in reducing the number of patient companions in the emergency ward during the COVID-19 outbreak. A comprehensive set of interventions was carried out including the establishment of hospital Wetchat platform, implementation of visual inter-conversation door-entry control system, enhancing the screening of attendants, improving the nursing quality, strengthening the concept of unattended severe and adopting ICU Visiting based on cloud technology. The aim of multi-dimensional team cooperation management was to reduce the number of patient companions, as well as risk of cross-infection in the ward during the COVID-19 outbreak. (本文总结了新型冠状病毒肺炎疫情防控期间科室多维度团队协作管理措施及实践效果, 通过医院公众订阅号、病房门禁可视对话系统、病房门岗岗位设置、提升护理服务水平、加强无陪护理念以及急诊ICU的“云探视”等干预策略来减少陪护人数, 从而降低病区内医、护、患及家属交叉感染的风险。)